2007
DOI: 10.1088/0022-3727/40/19/030
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of elastic-contact friction of transition metals under light loads based on their electron work functions

Abstract: Adhesion and light-load friction are crucial to the effective operation of nano/micro-devices, which are dependent on physical and mechanical properties of two metals in contact. Electron work function (EWF) and elastic modulus of metals have been demonstrated to be dominant parameters for adhesion and light-load friction of metals. This paper presents the authors' recent studies to correlate the elastic properties of metal with the EWF. It is demonstrated that there exists a strong correlation between EWF and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Thus, EWF is a fundamental property that could be used to predict and evaluate the mechanical behavior of metals. Previous studies [7][8][9][10][11][12][13][14] have demonstrated that mechanical properties of metals can be correlated to their electron work functions. For instance, Young's moduli, yield strength, and hardness of pure metals have a six-power relationship with their EWFs.…”
mentioning
confidence: 99%
“…Thus, EWF is a fundamental property that could be used to predict and evaluate the mechanical behavior of metals. Previous studies [7][8][9][10][11][12][13][14] have demonstrated that mechanical properties of metals can be correlated to their electron work functions. For instance, Young's moduli, yield strength, and hardness of pure metals have a six-power relationship with their EWFs.…”
mentioning
confidence: 99%
“…-(i) the thickness [48] and orientation [49] of grafted molecules at the macro- [50] and nanoscale [51]: That means that the CPD continuously increases with the packing density of SAM [52] ; -(ii) the grafting success [53]: the larger the CPD difference vs. the reference bias (CPD Si = 0 V), the stronger the molecules adhere onto the silicon substrate; -(iii) the surface reactivity for a given surface [44]: the more negative of the CPD measurement the higher the surface reactivity, according to the reactivity of the reference. In our case, any positive rise of the CPD may be connected to a decrease of the surface reactivity vs. the bare silicon one [45]; -(iv) many other tribological properties as friction level or wear precursors detection in the sub-surfaces as reported by several authors [54,55], thus: Figure 4 compares the CPD of the three printed nanopatterned SAM samples with respect to the bare silicon one taken as the reference with 0 V bias:…”
Section: Kelvin Probe Analysismentioning
confidence: 52%
“…2 There is also evidence linking the work function of a metal surface to its friction coefficient. [3][4][5] Quasicrystals are metallic alloys having aperiodic atomic order. 6,7 Most quasicrystals exhibit forbidden rotational symmetries.…”
mentioning
confidence: 99%